EWSR1 regulates mitosis by dynamically influencing microtubule acetylation. Issue 16 (17th August 2016) - Wang, Yi-Long; Chen, Hui; Zhan, Yi-Qun; Yin, Rong-Hua; Li, Chang-Yan; Ge, Chang-Hui; Yu, Miao; Yang, Xiao-Ming
ABSTRACT: EWSR1, participating in transcription and splicing, has been identified as a translocation partner for various transcription factors, resulting in translocation, which in turn plays crucial roles in tumorigenesis. Recent studies have investigated the role of EWSR1 in mitosis. However, the effect of EWSR1 on mitosis is poorly understood. Here, we observed that depletion of EWSR1 resulted in cell cycle arrest in the mitotic phase, mainly due to an increase in the time from nuclear envelope breakdown to metaphase, resulting in a high percentage of unaligned chromosomes and multipolar spindles. We also demonstrated that EWSR1 is a spindle-associated protein that interacts with α-tubulin during mitosis. EWSR1 depletion increased the cold-sensitivity of spindle microtubules, and decreased the rate of spindle assembly. EWSR1 regulated the level of microtubule acetylation in the mitotic spindle; microtubule acetylation was rescued in EWSR1-depleted mitotic cells following suppression of HDAC6 activity by its specific inhibitor or siRNA treatment. In summary, these results suggest that EWSR1 regulates the acetylation of microtubules in a cell cycle-dependent manner through its dynamic location on spindle MTs, and may be a novel regulator for mitosis progress independent of its translocation.